Targeted Profiling of Arabidopsis thaliana Subproteomes Illuminates Co- and Posttranslationally N-Terminal Myristoylated Proteins. Issue 3 (16th February 2018) - Majeran, Wojciech; Le Caer, Jean-Pierre; Ponnala, Lalit; Meinnel, Thierry; Giglione, Carmela
Abstract : This study demonstrated N -myristoylation of 72 proteins and identified hundreds of myristoylated proteins in different membrane networks using a targeted MS approach. Abstract: N-terminal myristoylation, a major eukaryotic protein lipid modification, is difficult to detect in vivo and challenging to predict in silico. We developed a proteomics strategy involving subfractionation of cellular membranes, combined with separation of hydrophobic peptides by mass spectrometry-coupled liquid chromatography to identify the Arabidopsis thaliana myristoylated proteome. This approach identified a starting pool of 8837 proteins in all analyzed cellular fractions, comprising 32% of the Arabidopsis proteome. Of these, 906 proteins contain an N-terminal Gly at position 2, a prerequisite for myristoylation, and 214 belong to the predicted myristoylome (comprising 51% of the predicted myristoylome of 421 proteins). We further show direct evidence of myristoylation in 72 proteins; 18 of these myristoylated proteins were not previously predicted. We found one myristoylation site downstream of a predicted initiation codon, indicating that posttranslational myristoylation occurs in plants. Over half of the identified proteins could be quantified and assigned to a subcellular compartment. Hierarchical clustering of protein accumulation combined with myristoylation and S -acylation data revealed that N-terminal double acylation influences redirection to the plasma membrane. In a few cases, MYR function extended beyond simple membrane association. This study identified hundreds of N -acylated proteins for which lipid modifications could control protein localization and expand protein function.